Syncronization Technology for The Reproductive Management in Sambar Deer (Rusa Unicolor Brookei) - Dradjat, AS; Semiadi, G (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
Research to study the synchronization technology to improve the reproductive of captive sambar deer (Rusa unicolor brookei) was conducted using 10 hinds and three stags aged 8 -10 years. Estrous induction was done using local intravaginal spon containing 450 mg Medroxy progesterone acetate (MPA), inserted the intravaginaly for 9 days. At 2 to 6 days post-sponge withdrawal, hinds were put together with stags in hard antler conditions. The results showed that retention rates of sponge reached 100% and no sign of irritation on the vagina. Two days post sponge withdrawal. Three hinds showed an estrous behavior and were mated, whereas four other hinds showed estrous behavior three days post sponge withdrawal. Overall 90% of hinds gave fawns at the end of pregnancy whit length of gestation 235,66 Â± 3,60 days (SD). It can be concluded that synchronization using locally made sponge showed a positive response in sambar deer. (Animal Production 11(1): 23-27 (2009)Â Key Words: Sambar deer, Intravaginal spong, Oestrus synchronisation